Knowledge, Perceived Self-care Ability, and Health Behavior in New Normal Era among Adults in Congested Communities of Surabaya, Indonesia: Impacts of COVID-19 Pandemic Situation - Ni Putu Wulan Purnama Sari; Jintana Artsanthia (Journal of Educational, Health and Community Psychology, 2022)
Health behavior in the COVID-19 pandemic situation needs to be measured in the general population to evaluate the implementation of health guidelines in the new normal era, especially WHO recommendations. Knowledge, attitude, and action are domains of health behavior translated into COVID-19 knowledge, perceived self-care ability, and new normal health behavior in this study. We aimed to describe the knowledge of COVID-19 and the perceived self-care ability and analyze the differences in new normal health behavior before and after the COVID-19 pandemic situation among adults living in congested communities of Surabaya, Indonesia. This cross-sectional study involved 384 respondents living in five congested communities of Surabaya, Indonesia, which enrolled utilizing random cluster sampling. Self-developed valid and reliable questionnaires measured research variables. Descriptive statistics and Wilcoxon signed rank test were used in data analysis. Ethical clearance was issued. Results showed that most respondents had very good knowledge of COVID-19 (63%) and a high level of perceived self-care ability (74%). Before and after the pandemic, most respondents reported sufficient new normal health behavior (before: 74.7%; after: 83.9%). There was a significant difference in new normal health behavior before and after the COVID-19 pandemic among adults living in congested communities of Surabaya, Indonesia (p=0.000). New normal health behavior was nonoptimal in implementation. Therefore, efforts to improve new normal health behavior need to be made by various parties, not only the individuals but also health care professionals and the government as policymakers.Keywords: COVID-19, health behavior, knowledge, pandemic,                              self-care